Loss of nitrogen from decomposing nodules and roots of the tropical legume Centrosema pubescens to soil - Chulan, Azizah; Waid, John S. (Australian Academy of Science, 1981)
Samples (20 g) of an air-dry, sieved (<2mm) silty loam with or without (controls) the incorporation of 200 mg root portions of Centrosema pubescens, were moistened to 50% moisture holding capacity at 0.33 bar (33 kPa). The root portions were healthy, freshly harvested, clean samples of nodules, laterals or radicles; treatments Nod, Lat and Rad respectively. Soil samples were incubated aerobically at 30 C for 16 weeks. The radicles, laterals and nodules respectively contained 1.65, 3.46 and 6.91 mg N per sample and their C to N ratios were 16.5, 7.0 and 4.2. The root fragments disappeared rapidly and less than 40% and 10% of their initial dry weight remained after 1 and 16 weeks respectively; nodules decomposed more rapidly than laterals and laterals more quickly than radicles. At 16 weeks the total N contents of the controls had not changed but Rad, Lat and Nod soils respectively showed gains over the controls from week 1 onwards and by week 16, these amounted to 8.2, 17.1 and 31.8%. Concentrations of mineral N increased in all soils from week 4 onwards and by week 16, the amounts of mineral N that had accumulated in Nod, Lat and Rad were 1.62, 1.16 and 1.14 times greater than in the controls (201 ~ N g-l oven-dry soil). Under the conditions of this experiment, the legume root and nodule tissues discomposed rapidly and all of the legume root N (except an unaccounted for 5.6% of the nodule N) was transferred to the soil without any apparent net loss or gain of volatile N.